2020
DOI: 10.1097/pas.0000000000001486
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Metaplasia of the Vagina and Uterine Cervix

Abstract: Prostatic-type differentiation in the lower female genital tract is encountered rarely and its causes and clinical associations are not well established. Within the vagina, reports to date have invariably described ectopic prostatic-type differentiation as restricted to the lamina propria. We recently encountered a patient receiving testosterone for gender dysphoria whose vaginectomy specimen showed a prostatic glandular proliferation within the surface epithelium. To elucidate its potential association with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…NKX.3.1 was also expressed in glandular structures within the exocervical squamous epithelium (Figs. 3A, B); these features have been previously reported in transgender men using exogenous testosterone (3)(4)(5). As a positive control, we confirmed that NKX3.1 was positive in prostate acinar cells and NKX3.1 positive cells were completely absent in 5 cases of endometrioid endometrial carcinoma (Supplementary Fig.…”
Section: Pathologic Findingssupporting
confidence: 87%
See 2 more Smart Citations
“…NKX.3.1 was also expressed in glandular structures within the exocervical squamous epithelium (Figs. 3A, B); these features have been previously reported in transgender men using exogenous testosterone (3)(4)(5). As a positive control, we confirmed that NKX3.1 was positive in prostate acinar cells and NKX3.1 positive cells were completely absent in 5 cases of endometrioid endometrial carcinoma (Supplementary Fig.…”
Section: Pathologic Findingssupporting
confidence: 87%
“…To the best of our knowledge, this is the first report of an endometrial cancer with NKX3.1 positivity in a transgender man. There have been several reports in recent years of histologic changes in the uterus and adnexa of FTMs that are believed to be caused by exogenous testosterone (3)(4)(5)(6)(7)(8). However, there are few reports of cancer in FTMs (9,10), and the relationship between exogenous testosterone and cancer in FTMs has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our included donors were presurgically exposed to testosterone for mean=5,9 (range 2-11) years, with no vaginal atrophy (thinned squamous epithelium) or prostatic metaplasia (epithelial or subepithelial stroma glands) present in our samples. Induced structural alterations have been reported as prostatic metaplasia in 7 MtF-patients (18-34 years) after 24-72 months of presurgical exposure to testosterone cypionate and metastatic glands located predominantly in epithelial layers [133] or as 80% atrophy, 40% urothelial metaplasia and 70% prostate-like glands in 10 MtF-patients (22-74 years) after 2-10 years of preoperative androgen receival [134].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, assigned female at birth (AFAB) persons have shown some evidence of prostatic tissue growth following extended testosterone therapy [198]. 18 Such is the case following many forms of chest reconstruction or contouring, in which there is still a chance of chest cancer because some tissue is left behind post-mastectomy [199,200].…”
mentioning
confidence: 99%